Effectiveness of Canada’s Employment Equity Legislation for Women (1997-2004): Implications for Policy Makers - C. Jain, Harish; J. Lawler, John; Bai, Bing; Lee, Eun (Relations industrielles / Industrial Relations, 2010)
This study focuses on the effectiveness of the federal Employment Equity Act (EEA). We assess the EEA with regard to female employees using quantitative data from employer reports published under the provisions of the EEA and the Canadian Census. Data in this study cover the period 1997 to 2004.Women constitute the largest of the designated groups, so the effectiveness of the law could have major implications for the welfare of a significant proportion of the Canadian workforce. The most significant finding is that employment equity has increased over time, but at a diminishing rate. In fact, there may be something of a downturn in employment equity for women in the industries covered by the EEA.It is clear from our analysis that women employees in the companies covered by the EEA continue to be under-represented, especially in large companies. Monitoring and enforcement of employment equity in these firms by the Canadian Human Rights Commission (CHRC) needs to be undertaken and is essential, since it cannot be taken for granted that larger firms do well in employment equity, overall. Our results and analysis indicate that smaller firms had higher employment equity than larger firms. It may also be necessary for the CHRC to examine the particular occupational groups within larger companies where employment equity is either low or non-existent relative to the Census.The continuing underlying pattern of sex segregation has changed to only a limited extent. For instance, employment opportunities for women continue to be problematic (that is, senior managers, skilled crafts and trades workers) and will require continued and perhaps intensified efforts to resolve. There are large discrepancies between employment equity in primary (i.e., full-time, permanent jobs) and secondary (i.e., temporary and part-time jobs), with employment equity being much lower in the primary sector. Human Resources and Social Development Canada need to have active labour market policies to correct this imbalance.